2021
DOI: 10.3390/pathophysiology28020014
|View full text |Cite
|
Sign up to set email alerts
|

Critically Ill COVID-19 Patients Exhibit Anti-SARS-CoV-2 Serological Responses

Abstract: Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, is a global health care emergency. Anti-SARS-CoV-2 serological profiling of critically ill COVID-19 patients was performed to determine their humoral response. Blood was collected from critically ill ICU patients, either COVID-19 positive (+) or COVID-19 negative (−), to measure anti-SARS-CoV-2 immunoglobulins: IgM; IgA; IgG; and Total Ig (combined IgM/IgA/IgG). Cohorts were similar, with the exception that COVID-19+ patients had a greater body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…23. Other studies have also reported the delayed B cell responses in Severe COVID-19 patients [19,21,23,24]. 24.…”
Section: Asymptomatic Covid-19 Patients Have Early Tregsmentioning
confidence: 89%
“…23. Other studies have also reported the delayed B cell responses in Severe COVID-19 patients [19,21,23,24]. 24.…”
Section: Asymptomatic Covid-19 Patients Have Early Tregsmentioning
confidence: 89%
“…Fraser et.al found that COVID-19+ patients who died had earlier/similar peaks in IgA and total Ig in their ICU stay when compared with the patients who have survived [24]. Critically ill COVID-19 patients exhibit anti-SARS-CoV-2 serological responses, including those COVID-19 patients who ultimately died, suggesting that blunted serological responses did not contribute to mortality [24].…”
Section: Delayed Humoral Responses In Severe Covid-19 Patientsmentioning
confidence: 99%
“…COVID-19 has been associated with hyper inflammation [10][11][12][13][14][15][16][17][18] and delayed humoral immune respo--nses [19,20,21,22,23,24]. Most of the complications with COVID-19 patients have been associated with early hypoxia, ARDS, pneumonia [60,77, [35][36][37][38][39] and Acute Lung Injury [30][31][32][33][34].…”
Section: Sars-cov-2 Induces Delayed Humoral Responses and Accelerated Innate Immune Response Mediated Damagesmentioning
confidence: 99%
See 2 more Smart Citations